Peripheral markers in neurodegenerative patients and their first-degree relatives - Cristalli, Diana Olga (2012)
We have determined various biomarkers in the peripheral blood of Alzheimer, Parkinson and vascular dementia patients by comparing the samples with those of first-degree relatives and control subjects. Our results, together with correlation studies using data from the Mini-Mental State Examination (MMSE), suggest that the clinical evaluation of the nitrite (NOx) concentration in Alzheimer patients should be complemented by assays of protein carbonyls (PCs) levels, the ratio of reduced to oxidized glutathione (GSH/GSSG) in plasma, PCs in erythrocytes and PCs and calcium content in leukocytes. For Parkinson patients it would be useful to determine NOx, thiobarbituric-acid reactive substances (TBARS) and PCs in erythrocytes, and NOx and TBARS en leukocytes. For vascular-demented (VD) patients, determination of NOx, Cu, and GSH/GSSG in plasma and TBARS, and PCs in erythrocytes together with PCs in leukocytes should be assayed. Relatives of Alzheimer patients showed alterations in plasma Se and Zn concentrations, catalase (CAT) activity in erythrocytes and calcium content in leukocytes as possible predictive markers of the disease. Relatives of Parkinson patients showed elevated levels of NOx in leukocytes. In the case of vascular-demented patients we suggest NOx, GSH/GSSG and α-tocopherol in plasma, the CAT/superoxide dismutase ratio in erythrocytes and TBARS, GSSG and glutathione reductase in leukocytes as predictive markers. Large-scale longitudinal population-based studies using these suggested biomarkers are necessary in order to assess their level of reliability and specificity in clinical practice.